MAHKOTA INDUKSI KOLKISIN PADA KALUS BUNGA Hibiscus rosasinensis L. DAN PROFIL KROMATOGRAFI LAPIS TIPISNYA - , RATIH ANGGAR KUSUMANINGTIYAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research of colchicine induction at shoe flower petal callus has been carried. The research purpose is to know the effect of colchicine addition in liquid MS media and to know its chromatogram profile of shoe flower callus compared to primary plant. Steril petal bud plants in solid MS media+2,4-D 1 ppm. The 4-week old callus is separated from explant and subcultured in liquid MS+colchicine at concentration 2,5x10-3 M by incubation variation of 24, 48, 72 hours, harvested then. As control is callus incubated in liquid MS media without colchicine in 72 hours. Several cuts of callus is observed to see its cell division and the rest of callus is analyzed by TLC to see chemistry content of eternal potential. The substance responsible for colour variation in petal is anthocyanine. Anthocyaninecan be identified by ammonia fume, FeCl3 and anisaldehyde-sulphuric acid. Callus induction for 48 hours has polygonal cell shape with 1 nucleus, 2 nucleuses and 3 nucleuses, meanwhile, the induction of 24